Role of antibodies against biotype-specific Vibrio cholerae pili in protection against experimental classical and El Tor cholera. - Osek, J (1994)
Vibrio cholerae O1, which exists as two biotypes, classical and El Tor, expresses fimbrial antigens called toxin-coregulated pili (TCP) and mannose-sensitive hemagglutinin (MSHA) pili, respectively. We have raised rabbit antisera and monoclonal antibodies against these fimbrial antigens and prepared Fab fragments which possess specific antibodies directed against the respective fimbrial antigens from these antisera. The protective effect of these antibody preparations was studied in the infant mouse cholera model. Antibodies against TCP were able to protect baby mice against challenge with V. cholerae O1 of the classical but not of the El Tor biotype. Similar but reverse biotype differences in protection against challenge with classical and El Tor vibrios were observed when antibodies against MSHA pili were used. The protective effect of V. cholerae O1 antilipopolysaccharide (anti-LPS) antibodies, both alone and in combination with antifimbrial antibodies, was also evaluated. We showed that antibodies to the LPS component also prevented infections with V. cholerae O1. Moreover, our results indicate that antibodies against TCP or MSHA pili and against LPS cooperate at least additively, and possible even synergistically, in protecting baby mice against challenge with group O1 vibrios. These results indicate that TCP and MSHA pili as well as LPS play an important role in the pathogenesis of experimental cholera. We could also demonstrate that antibacterial immunity preventing colonization is biotype specific. Our results might be used for the generation of new oral cholera vaccines including both TCP and MSHA fimbrial antigens.